Modeling the Effect of Temperature-induced Surface Tension Gradient in Coating Processes - Abdullah, Bawadi; Vo, Dai-Viet N.; Chowdhury, Sujan (Trans Tech Publications, Switzerland, 2014)
The coating of the fluorescent-lamp material inside the fluorescent tube is prone to defect such as dark line formation. A one-dimensional mathematical model based on Navier-Stokes equation, which describes the flow of drying coating on horizontal planar substrates, was developed to investigate the defect formation. The effect of temperature distribution on surface tension gradient was incorporated into the model, to quantify defect formation in drying coating. The results showed that, temperature-induced surface tension gradient plays a major role in defect formation while the effect of pressure gradient is insignificant. The evaporation rate and viscosity affect the defect thickness and spread, and also the defect formation time. The temperature gradient seems to have the largest influence on surface tension gradient, thus defect formation. The model developed can be used as a process analysis tool in industrial applications of fluorescent tube coating.